A growing challenge: The rise of femoral periprosthetic fractures – An 11-year observational study. Issue 1 (February 2020) - Fenelon, C.; Murphy, E.P.; Kearns, S.R.; Curtin, W.; Murphy, C.G.
Abstract: Introduction: The demand for joint arthroplasty has risen as our elderly population increases and ages. With this so to has the number of patients suffering periprosthetic fractures (PPF). The aim of our study was to quantify the burden of PPF and provide an up to date reference of the epidemiology of PPF in Ireland. We also sought to assess length of stay (LOS), resource utilisation and mortality associated with this cohort of patients. Methods: An eleven-year retrospective observational study was conducted of a consecutive series of patients treated for a femoral PPF. Costs were obtained from activity based tariffs provided by the hospital inpatient enquiry system and mortality was confirmed using the national death events publication system. Results: Over the 11-year study period 174 procedures for a femoral PPF were performed. Mean age of patients was 77.6 years (SD 11.1 years) with 44.7% male. Median ASA grade was 3 (range 1–4) and mean LOS was 19 days. There was a 700% increase in patients undergoing surgery for a PPF over the study period. The mean cost of care was €24, 413 in 2017. Thirty-day mortality was 2.9% while one-year mortality was 12.4%. Conclusions: PPF occur in an elderly comorbid cohort of patients. Care of these patients now makes up a considerable part of the orthopaedic workload and consumes a significant portion of healthcare resources. Patients should be treated in tertiary referral centres with surgeons skilled in their management. Better access to rehabilitation is needed.